The Effects of BITs on Contract Execution in Developing Countries: Some Implications for the COVID-19 Crisis - Yu, Zhihan; Zhou, Chao; Wang, Qin; Hu, Ke; Su, Ke; Zhang, Mengqi (Frontiers in Public Health, 2022)
Bilateral investment agreements are bilateral treaties between capital exporting countries and host countries, which is specially used to protect international investment, and the contract execution is directly related to the daily operation of multinational enterprises. Based on the panel data of 73 developing countries from 2005 to 2019, this paper examines the improvement effect of BITs on the contract execution of host countries. The study found that both the overall bilateral investment agreements and the bilateral investment agreements in force can significantly improve the contract execution of the host country. Due to the differences between the civil law system and the common law system in many aspects, such as the source of evidence and trial mode, the effect of BITs on the improvement of contract execution in host countries of the common law system is more prominent. In terms of specific impact, the improvement effect of BITs on time is significantly better than cost. The core conclusion is still valid after changing the estimation method and eliminating abnormal samples.